OP0199-PARE Support to stay employed and social security arrangements for work disability due to ra – perceptions of patients with ra and rheumatologists in 31 european countries. (15th June 2017) - Putrik, P; Ramiro, S; Guillemin, F; Rojkovich, B; Sivera, F; Wit, M de; Woolf, A; Zink, A; Sokka, T; Boonen, A; ,
Abstract : Background: Despite demonstrated influence of country of residence on labour force participation among patients with RA, little attempt has been made to understand the users' perceptions of support and social security (SS) systems. Objectives: To explore the patterns in perceptions among patients with RA and rheumatologists from different European countries across five domains (1) importance and support to remain employed, (2) process of applying for WD, (3) obtaining and living with WD pension, (4) role of the rheumatologists in support to remain employed or apply for WD pension and (5) performance of the system. Methods: A survey among RA patients and rheumatologists was conducted in 44 countries of European WHO Region. For each domain, several questions (4 to 6 questions per domain, each on a 1–5 Likert answer scale, dichotomized as 1 ("totally (agree)") and 0 ("not agree, not disagree", "totally (disagree)") were asked (Table). Next, sum scores were calculated for each domain and averaged per country. The domain "remaining employed" was assessed in patients who currently have or ever had work. Analyses in domains "process of applying for WD" and "obtaining and living with WD" were limited to patients who currently have or ever considered applying for WD. Comparisons of scores in all domains were explored by: EU-15, new EU member states and non-EU countries, the five types of social welfare system (Anglo-Saxon, Bismarckian, Mediterranean, Post-Communist, and Scandinavian) and by countries' wealth (GDP per capita adjusted for purchasing power parity [PPP]) using ANOVA or Pearson correlation, as appropriate. Results: Of 44 countries, 31 (70%) and 30 (68%) have provided data for patients and rheumatologists, respectively. In total, 646 patients (mean age (SD) 53 (12), 76% female, 519 (78%) ever worked) and 500 rheumatologists filled in the questionnaires. Overall, positive weak to no relationships were present between the GDP per capita and perceptions from rheumatologists or patients about SS arrangements. However, significant differences were observed across the systems type with the Scandinavian type (Finland, Norway, Sweden) consistently scoring higher than the others on most domains (table). Remarkably, rheumatologists in less wealthy and non-EU countries felt more confident in their role related to WD pension. Conclusions: Patients'a nd rheumatologists' perceptions of systems to support persons with RA encountering work restrictions varied mostly according to the type of the social welfare system, while remarkably little differences were related to country's wealth and membership in EU. Scandinavian employment support and social security system appeared to most adequately meet the expectations of patients and rheumatologists in questions of remaining at work and application to WD pension. Disclosure of Interest: None declared